Optimized strength and conductivity of multi-scale copper alloy/metallic glass composites tuned by a one-step spark plasma sintering (SPS) process. (20th November 2022) - Bao, Weizong; Chen, Jie; Xie, Guoqiang
Highlights: High strength and high conductivity multi-scale metallic glass composites were fabricated by a one-step spark plasma sintering (SPS). The contribution of multi-scale structure and excellent interface bonding to properties is characterized and discussed. Abstract: A superiority in interfacial bonding is favorable to fabricate high-strength conductive composites for electrical contact applications. In the present work, high strength and high conductivity multi-scale metallic glass composites (including micron-scale CuZrAl metallic glass reinforcement, hundred-nanometer-scale CuCrZr crystalline grain matrix, and nano-scale precipitated phase) were fabricated by a one-step spark plasma sintering (SPS). The strength and conductivity of the bulk copper matrix metallic glass composites (BCMGCs) were enhanced simultaneously with the increase in the sintering pressure of the SPS. The excellent performance is attributed to the improved interfacial bonding between the metallic glass reinforcement and the copper alloy matrix due to the high pressure assisted by temperature and pulsed current. In particular, the precipitation of nanoprecipitates at the interface further reduces the interfacial resistance and improves the mechanical properties of the composites. This work broadens the horizon for the selection and optimization of reinforcements and manufacturing processes for high-performance electrical contact materials (ECMs). Graphical abstract: Image, graphical abstract